1989
DOI: 10.1111/j.1600-0447.1989.tb01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary‐adrenal and ‐thyroid axis dysfunctions and decrements in the availability of L‐tryptophan as biological markers of suicidal ideation in major depressed females

Abstract: Several neurochemical correlates of suicide were recently detected. Some authors found increased disorders in the hypothalamic-pituitary-adrenal (HPA) and -thyroid (HPT) axes and disturbances in serotonergic neurotransmission in suicidal patients. In order to investigate the biological correlates of suicidal ideation, we measured the following: basal thyrotropin-secreting hormone (TSH), free thyroxine (FT4), pre- and postdexamethasone cortisol, adrenocorticotropic hormone (ACTH) levels, the circulating concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…In other disasters, such as, earthquakes and storms, there is a gradient of destruction from the epicenter. The Enschede fireworks factory disaster affected people who came from a defined geographical region [21, 22]. In these circumstances, disaster services should be carefully integrated with the existing primary and secondary health care networks that particular people use at such times.…”
Section: Types Of Disastersmentioning
confidence: 99%
“…In other disasters, such as, earthquakes and storms, there is a gradient of destruction from the epicenter. The Enschede fireworks factory disaster affected people who came from a defined geographical region [21, 22]. In these circumstances, disaster services should be carefully integrated with the existing primary and secondary health care networks that particular people use at such times.…”
Section: Types Of Disastersmentioning
confidence: 99%
“…Based on the included studies, there may be associations between neuropeptides and suicidal behavior but this does not imply the existence of a causal link. Most studies (thirtheen) [33, 34, 8385, 89, 90, 9296, 101] included in our review found an association between neuropeptides and suicidal behavior; however, there are also six studies [86, 91, 98100, 102] that did not confirm this association. Moreover, there are other studies suggesting that neuropeptides abnormalities may be found in subjects with MDD but not suicidal behavior [87, 88, 97].…”
Section: Discussionmentioning
confidence: 88%
“…Also, Ordway et al [99] found no significant differences in NPY concentrations between suicide victims with MDD (with comorbid alcohol dependence) and age-matched control subjects. Finally, Maes et al [102] reported no significant differences in TSH, FT4, ACTH, and total L-TRP levels between patients with suicidal ideation and those without.…”
Section: Resultsmentioning
confidence: 99%
“…PTSS-10 is a 10-item scale, which measures posttraumatic stress symptoms including hyperarousal on a Likert scale where 1 represents "never/seldom" and 7 represents "very often", with scores ranging from 10 to 70 [5,18,19]. …”
Section: Methodsmentioning
confidence: 99%